2015
DOI: 10.2174/1874325001509010194
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence in Collarless Corail Hip Replacement

Abstract: The purpose of this study was to assess whether subsidence occurs in collarless Corail hip replacement (CCHR) and to ascertain the extent and timing of subsidence if present. Retrospective case notes analysis was performed. Sixty eight patients who had CCHR were identified from our database. Male to female ratio was 32:36. Their mean age was 74.2 years (range 37-95 years). Indications for surgery were osteoarthritis in 64 (94%) patients, rheumatoid arthritis in two (3%) patients and avascular necrosis in two (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Thus, any malpositioning of the cup cannot always be sufficiently adjusted for with the stem. Also, the uncemented stem may subside in the femur more often than cemented ones (Selvaratnam et al 2015). It may be that these factors lead to suboptimal position of the THA components, and thus to a higher risk of revision due to dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any malpositioning of the cup cannot always be sufficiently adjusted for with the stem. Also, the uncemented stem may subside in the femur more often than cemented ones (Selvaratnam et al 2015). It may be that these factors lead to suboptimal position of the THA components, and thus to a higher risk of revision due to dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…The collared options were designed with the goal of limiting subsidence and providing rotational stability [7]. In addition, it is entirely coated with hydroxyapatite to block the release of metal ions and promote osseointegration with the endosteal surface [24].…”
Section: Introductionmentioning
confidence: 99%
“…6 Campbell et al reported a mean subsidence of 0.58 mm using collarless corail stems in a cohort of 30 patients using radiostereometric analysis, 7 whereas Selvaratnam et al reported more than 2 mm subsidence in 28% of their sample at 6 weeks post operatively, using the same stem. 8 Another parameter of interest is the risk of intraoperative femoral fracture, which has been reported ranging in 2.7-11% of cases. [9][10][11][12] Bonnin et al looked at the preoperative morphology of femur using CT scan in 100 cases of uncemented THA.…”
Section: Introductionmentioning
confidence: 99%
“…6 Campbell et al reported a mean subsidence of 0.58 mm using collarless corail stems in a cohort of 30 patients using radiostereometric analysis, 7 whereas Selvaratnam et al reported more than 2 mm subsidence in 28% of their sample at 6 weeks post operatively, using the same stem. 8…”
Section: Introductionmentioning
confidence: 99%